Prevalência de transtornos psiquiátricos menores em trabalhadores da atenção primária à saúde das regiões Sul e Nordeste do Brasil Prevalence of minor psychiatric disorders among primary healthcare workers in the South and Northeast regions of Brazil - Alitéia Santiago Dilélio; Luiz Augusto Facchini; Elaine Tomasi; Suele Manjourany Silva; Elaine Thumé; Roberto Xavier Piccini; Denise Silva Silveira; Maria de Fátima Santos Maia; Alessander Osório; Fernando Vinholes Siqueira; Vanda Maria da Rosa Jardim; Marcos Aurélio Matos Lemões; et al. (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2012)
Os problemas de saúde mental estão entre os mais prevalentes em trabalhadores de saúde. Foram avaliados a prevalência de transtornos psiquiátricos menores e os fatores associados em trabalhadores da atenção primária à saúde. O delineamento foi transversal com base em 240 unidades básicas de saúde de 41 municípios acima de 100 mil habitantes de sete estados das regiões Sul e Nordeste do Brasil. Foram entrevistados 4.749 trabalhadores, e a prevalência de transtornos psiquiátricos menores foi de 16%, sem diferenças estatísticas por região e modelo de atenção. Foi maior em agentes comunitários de saúde e outros trabalhadores de nível médio (18%), menor em outros profissionais de nível superior (10%), ficando médicos (15%) e profissionais de enfermagem (14,6%) em posição intermediária (p < 0,001). As características ocupacionais apresentaram a mais forte associação com a ocorrência de transtornos psiquiátricos menores na análise ajustada, sugerindo que sua redução depende de melhorias nas condições de trabalho na atenção primária à saúde e na gestão do Sistema Único de Saúde. Mental health problems are among the most prevalent conditions in health workers. We evaluated the prevalence of minor psychiatric disorders and associated factors among primary healthcare workers. The study design was cross-sectional and services-based, in 240 primary healthcare units in 41 municipalities (counties) with more than 100 thousand inhabitants in seven States in the South and Northeast regions of Brazil. A total of 4,749 primary healthcare workers were interviewed, and prevalence of minor psychiatric disorders was 16%, with no statistical differences according to region or primary care model. The rate was higher in community health workers and other workers with secondary education (18%) and lower in health professionals with university training (10%); while physicians (15%) and nurses and nurse technicians (14.6%) were in an intermediate situation (p < 0.001). Occupational characteristics showed the strongest association with the occurrence of minor psychiatric disorders according to the adjusted analysis, suggesting that their reduction requires improvements in work conditions in primary healthcare and in the management of the Unified National Health System.